Exploring the Integration of STEAM Education in Senior High School Chinese Language Teaching-taking “Yiwu Mechanical and Electrical Technician High School” as a Case Study - Qiuying, Wang; Wai Yie, Leong (INTI International University, 2024)
This paper explores the integration of STEAM (Science, Technology, Engineering, Arts, and Mathematics) education into senior high school Chinese language teaching, using Yiwu Mechanical and Electrical Technician High School as a case study. The study investigates how the incorporation of STEAM elements enhances students’ engagement, critical thinking, and language skills by embedding creative and interdisciplinary approaches into traditional Chinese language curricula. By adopting project-based learning, digital storytelling, and interactive activities, the program seeks to foster a deeper appreciation for Chinese language and literature while promoting skills relevant to the 21st century, such as problem-solving, collaboration, and innovation. Qualitative data, including classroom observations, teacher interviews, and student feedback, reveal that integrating STEAM education in language arts encourages students to view language as a dynamic tool for exploration rather than a static subject. The study showed that many teachers were willing to participate in relevant training even though they were unfamiliar with STEAM education concepts. Chinese language teaching in senior high schools based on the STEAM concept significantly enhances students' interest and learning outcomes, and promotes the cultivation of interdisciplinary thinking and innovative abilities. Therefore, it is important to continue to improve this teaching model to promote the reform of Chinese language teaching.